Exclusive diffractive resonance production in proton-proton collisions at high energies - Fiore, Roberto; Jenkovszky, László; Schicker, Rainer (The European physical journal. C, Particles and fields, 2018)
A model for exclusive diffractive resonance production in proton-proton collisions at high energies is presented. This model is able to predict double differential distributions with respect to the mass and the transverse momentum of the produced resonance in the mass region $$\sqrt{M^2}\lesssim $$M2≲5 GeV. The model is based on convoluting the Pomeron distribution in the proton with the Pomeron-Pomeron-meson total cross section. The Pomeron-Pomeron-meson cross section is saturated by direct-channel contributions from the Pomeron as well as from two different f trajectories, accompanied by the isolated f$$_0(500)$$0(500)resonance dominating the $$\sqrt{M^{2}}\lesssim 1$$M2≲1GeV region. A slowly varying background is taken into account.